Comparative proteomic analysis of human milk fat globules and paired membranes and mouse milk fat globules identifies core cellular systems contributing to mammary lipid trafficking and secretion - Martin Carli, Jayne F.; Dzieciatkowska, Monika; Hernandez, Teri L.; Monks, Jenifer; McManaman, James L. (Frontiers in Molecular Biosciences, 2023)
Introduction: Human milk delivers critical nutritional and immunological support to human infants. Milk fat globules (MFGs) and their associated membranes (MFGMs) contain the majority of milk lipids and many bioactive components that contribute to neonatal development and health, yet their compositions have not been fully defined, and the mechanisms responsible for formation of these structures remain incompletely understood.In this study, we used untargeted mass spectrometry to quantitatively profile the protein compositions of freshly obtained MFGs and their paired, physically separated MFGM fractions from 13 human milk samples. We also quantitatively profiled the MFG protein compositions of 9 pooled milk samples from 18 lactating mouse dams.We identified 2,453 proteins and 2,795 proteins in the majority of human MFG and MFGM samples, respectively, and 1,577 proteins in mouse MFGs. Using paired analyses of protein abundance in MFGMs compared to MFGs (MFGM-MFG; 1% FDR), we identified 699 proteins that were more highly abundant in MFGMs (MFGM-enriched), and 201 proteins that were less abundant in MFGMs (cytoplasmic). MFGM-enriched proteins comprised membrane systems (apical plasma membrane and multiple vesicular membranes) hypothesized to be responsible for lipid and protein secretion and components of membrane transport and signaling systems. Cytoplasmic proteins included ribosomal and proteasomal systems. Comparing abundance between human and mouse MFGs, we find a positive correlation (R 2 =0.44, p<0.0001) in the relative abundances of 1,279 proteins that were found in common across species.Discussion: Comparative pathway enrichment analyses between human and mouse samples reveal similarities in membrane trafficking and signaling pathways involved in milk fat secretion and identify potentially novel immunological components of MFGs. Our results advance knowledge of the composition and relative quantities of proteins in human and mouse MFGs in greater detail, provide a quantitative profile of specifically enriched human MFGM proteins, and identify core cellular systems involved in milk lipid secretion.